Evaluación de las cervezas artesanales de producción nacional y su maridaje con la cocina ecuatoriana - Quintana Lombeida, María Dolores (2018)
Ecuador is considered a country with high beer consumption, over other moderation drinks and is that the San Francisco Convent is known as the first beer in South America, according to Peralta Paredes (2013).The present investigation refers to two variables, the first generation with the growing emergence of the production of craft beers in Ecuador, which according to data from the newspaper Expreso (2017), this manufacture covers 5% of the demand for the beverage; It has been proposed to identify the sensory profiles of this premium product through a random, descriptive -correlational study with the use of data collection instruments such as expert panels and observation.Regarding the second variable of analysis, referring to the national cuisine and its representative dishes; a bibliographic, random, analytical and deductive research was carried out that classified the preparations according to their origin and popularity for their later organoleptic description.By means of measurement evaluations, Sommelier certificates were applied to choose the theoretical methods of three beers, and of these the most appropriate combination between craft beer and the traditional Ecuadorian dish.The results found identified a twenty-two craft beers of local local production for pairing with the same number of dishes representative of the cuisine of Ecuador, where three of the four natural regions of the country and the preparations of their respective provinces are taken into account. Thei ntimate and aromatic